Investigating the differences between females perceive same-gender and heterogender sex robots regarding adoption and intentions - Li, Yuanjun (Frontiers in Psychology, 2022)
The market for sex robots is on the rise. Females are the main owners of sex products and they have better decision-making abilities and financial power in consumption nowadays. However, most sex robots on the market nowadays are presented as male-friendly products. This may limit and hinder female’s adoption and utilization of sex robots. This paper was to take females as the research subjects to explore and verify several concerns based on previous theories. To conduct primary research and quantitative method to investigate: (i) how females differently perceive same-gender and heterogender sex robots; (ii) their attitudes and the knowledge or definition of sex robots; (iii) their purchase intention towards heterogender robots. This study confirmed several previous theories, as well as provided new findings and market insights. Females are more likely to feel threatened by the presence of same-gender sex robots. Their negative attitude might be related to the way that sex robots exist. They consider sex robots as sexual products, and the purchase intention exists. Marketers should attach importance to female’s requirements of sex robots’ appearance.